Digestive plants of the Patagonian steppe: multidimensional variables that affect their knowledge and use - Molares, Soledad; Ciampagna, María Laura; Ladio, Ana (Ethnobotany Research and Applications, 2023)
Background: In a rural Mapuche community of the Patagonian steppe (Chubut, Argentina), we analyzed how the use and popularity of digestive plants are affected by their aroma, the presence of dual medicinal-edible uses, their digestive versatility, biogeographical origin and accessibility. Methods: Free listing and in-depth interviews were conducted with 25 collaborators, complemented with participant observation and walks in the field. Quantitative indices, non-parametric methods (Binomial and Chi-square tests, p < 0, 05) and generalized linear models (GLM, Omnibus test, p < 0, 05) were performed. Results: Local collaborators use 61 digestive plants, including a similar number of native and exotic species. Most are used for only one type of digestive use, are very accessible and have aroma. There are as many species with dual use as without dual use. Exotic species generally have more aroma than native ones. Only exotic species are highly accessible. Species with dual uses are mainly used as condiments. Digestive-only species could or could not have aroma. The popularity of species is only affected by their digestive versatility and aroma, mainly for exotic ones. Conclusions: Local pharmacopoeia reflects aspects that account for its cultural resilience, including a high richness of native and exotic digestive plants, many of which are used for specific ailments. The species have been selected from the joint evaluation of biophysical and sociocultural variables that influence their knowledge and forms of use. These variables and perceptions would also allow diversification in response to changes, forming part of a bio-cultural legacy unique to Patagonia. Keywords: Mapuche medicinal flora, Patagonia, popularity, cultural resilience.